Medical psychotherapy consultation: psychoanalytic psychiatry for the patient and professional. Issue 3 (2nd July 2016) - Johnston, James; Luthra, Vikram S.; Mzizi, Lackson; Cardno, Alastair
Abstract : An NHS Mental Health Trust Medical Psychotherapy Consultation Service using psychoanalytic psychiatry to help the patient and professional is described. The Consultation Service established in 2000 is offered to secondary acute and community mental health teams and primary care. The service was evaluated as a basis for regional and national development. Between 2006 and 2013, 87 consultations from 210 were sampled to ascertain demographic and diagnostic profiles and outcomes of the consultation process. We conducted an online survey of local consultant psychiatrists' views about the service, and undertook a thematic analysis of the free text comments. We also conducted a survey of members of the Royal College of Psychiatrists' Medical Psychotherapy Faculty to ascertain whether similar consultation services existed elsewhere in the UK and had been evaluated. The Leeds model of psychoanalytic consultation – a 'consultation sandwich' – is described. From a psychoanalytic perspective, the work of consultation is seen as an extension of the dynamic field of the analytic situation. This paper develops the concept of a bastion – an omnipotent reserve in and between the patient and professional derived from adhesive identifications leading to stuck relationships. The adhesive identification in the patient and professional acts like a 'grievance glue' – a mutual manifestation in a last bastion of painful limitations not faced, losses not grieved.